Răspuns :
Răspuns:
x = {- 6 ; 3)
Explicatie pas cu pas:
log2(x² + 3x - 10) = 3
x² + 3x - 10 = 2³ ⇔ x² + 3x - 10 = 8
x² + 3x - 10 - 8 = 0 ⇔ x² + 6x - 3x - 18 = 0
x(x + 6) - 3(x + 6) = 0 ⇔ (x + 6)(x - 3) = 0
x + 6 = 0 ⇒ x = 0 - 6 = - 6
x - 3 = 0 ⇒ x = 0 + 3 = 3
⇒x = {- 6 ; 3)
Răspuns:
3 și -6
Explicație pas cu pas:
[tex]log_{2}[/tex] ([tex]x^{2}[/tex] + 3x - 10) = 3
[tex]log_{2}[/tex] ([tex]x^{2}[/tex] + 3x - 10) = 3 · [tex]log_{2}[/tex] 2
[tex]log_{2}[/tex] ([tex]x^{2}[/tex] + 3x - 10) = [tex]log_{2}[/tex] ([tex]2^{3}[/tex])
[tex]x^{2}[/tex] + 3x - 10 = [tex]2^{3}[/tex]
[tex]x^{2}[/tex] + 3x - 10 = 8
[tex]x^{2}[/tex] + 3x - 10 - 8 = 0
[tex]x^{2}[/tex] + 3x - 18 = 0
Δ = [tex]3^{2}[/tex] - 4 (- 18) = 9 + 72 = 81
[tex]x_{1,2}[/tex] = (- 3 ± [tex]\sqrt{81}[/tex])/2
[tex]x_{1,2}[/tex] = (- 3 ± 9)/2
[tex]x_{1}[/tex] = (- 3 + 9)/2 ⇒ [tex]x_{1}[/tex] = 6/2 ⇒ [tex]x_{1}[/tex] = 3
[tex]x_{2}[/tex] = (- 3 - 9)/2 ⇒ [tex]x_{2}[/tex] = (-12)/2 ⇒ [tex]x_{2}[/tex] = -6